The Implementation of Interactive Game-Based Media "Adventure Motion Track" to Improve Students' Fundamental Movement Skills in Physical Education Learning Through Differentiated Instruction at SDN Kampungdalem 4 - Ridwan Ali Fahmi; Ruruh Andayani Bekti; Ali Masrofi (JURNAL ILMIAH NUSANTARA, 2025)
Physical education plays a crucial role in developing students' fundamental movement skills in elementary schools. However, the lack of variation in teaching methods often leads to low student participation and motivation. This study aims to implement and analyze the effectiveness of the interactive game-based media Adventure Motion Track in enhancing students' fundamental movement skills through differentiated learning at SDN Kampungdalem 4. This research employs a descriptive approach using both PTK. Data were collected through observations, interviews, and pre- and post-tests of fundamental movement skills. The results indicate that the implementation of Adventure Motion Track significantly improves students' fundamental movement skills. Furthermore, the game enhances student motivation, active participation, and social interaction in learning. In conclusion, this interactive game-based media is an effective and innovative teaching method in physical education. Through a differentiated learning approach, students can learn according to their abilities and needs, leading to more optimal learning outcomes.